Low-temperature CO preferential oxidation in H2-rich stream over iron modified Pd–Cu/hydroxyapatite catalyst. (23rd August 2021) - Li, Xiao; Xing, Lisha; Zhao, Wanjun; Wang, Yongzhao; Zhao, Yongxiang
Abstract: The effect of FeCl3 addition on the catalytic property of Pd–Cu/hydroxyapatite (Pd–Cu/HAP) for low-temperature CO preferential oxidation (CO-PROX) under H2 -rich condition has been investigated. It can be found that CO conversion of Pd–Cu/HAP rapidly decreases from 56% to 21% within 2 h at 30 °C in the presence of water, however, the Pd–Cu–Fe/HAP with the Fe/Cu atomic ratio of 1:1 presents a stable CO conversion of 40% and CO2 selectivity of 100% under the same reaction conditions. The characterization results display that the addition of FeCl3 to Pd–Cu/HAP causes the formation of Fe2 O3 species, and the strong interaction presents between Fe2 O3 species and Pd–Cu/HAP. Thus, the Pd 0 species generated during CO-PROX over Pd–Cu–Fe/HAP can be more easily oxidized than that over Pd–Cu/HAP, which could avoid H2 adsorption on Pd 0 species and maintain CO adsorption and activation. Graphical abstract: Image 1 Highlights: Pd–Cu–Fe/HAP exhibits the better catalytic performance than Pd–Cu/HAP for CO-PROX. The addition of FeCl3 to Pd–Cu/HAP causes the formation of Fe2 O3 species. There is a strong interaction between Fe2 O3 species and Pd–Cu/HAP. The Pd 0 generated during CO-PROX over Pd–Cu–Fe/HAP can be more easily oxidized. Pd–Cu–Fe/HAP avoids H2 adsorption on Pd 0 and keeps CO adsorption and activation.